Dampak Pencemaran Aktivitas Kendaraan Bermotor terhadap Kandungan Timbal (Pb) dalam Tanah dan Tanaman Padi - Listin Fitrianah; Muhammad Yani; Sobri Effendi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Increasing in volume and activity of motor vehicles cause to increasing in gasoline consumption and air pollutants such as lead (Pb). The lead in the ambient environment  will be deposited to the soil and absorbed by plants. The study was conducted to assess the lead content in soil and rice plant at rice field at Lamongan that caused by motor vehicles activities. The motor vehicles activities along Lamongan boulevard were identified and assess to lead emission.  The deposition of  lead from ambient were observed to soil, and rice plant at the road side (north and south) for 100, 1000, and 2000 m, and analyzed befor and after rice planting. The Lead content in rice plants highest at north side of 100 m, while the lowest was found in rice plant south side with a distance of 2000 m.  Lead content in the highest rice bean found in rice plant north side of 100 m, while the lowest was found in rice paddies south side of the road a distance of 2000 m.